A power sharing control for microgrids based on extrapolation of injecting power and power-angle control - Suchart Janjornmanit (2018)
© TÜBİTAK. Droop controlled power sharing with an assumption that the value of line impedance is unavailable has been proven to have limitations; the power sharing is problematic in systems with significantly resistive lines. Furthermore, when the droop is applied in the islanding mode of operation of a microgrid, the system is likely to become unstable. In this paper, the droop control is replaced by an analytical solution. The proposed approach of power sharing is powerangle control of distributed generators (DGs), such as voltage source converters, a type of DG with extrapolation of power injected to the connected bus. It is demonstrated that the power injection to the bus could be tracked within the DG's capacity autonomously. Simulation and experimental results demonstrate the validity of the approach and it is shown that the proposed approach is suitable for DGs with either inductive or resistive line impedance. Moreover, this method can be operated in complex networks, such as meshed networks.